Gendered pathways from academic performance, motivational beliefs, and school burnout to adolescents’ educational and occupational aspirations - Anna Widlund; Heta Tuominen; Anna Tapola; Johan Korhonen (Elsevier, 2022)
This study examined Finnish 9th-graders’ (N = 966) pathways to educational and occupational aspirations considering two academic domains: mathematics and reading. Multi-group structural equation models were conducted to investigate how domain-specific performance and motivational beliefs (self-concept and interest), and more general school burnout (exhaustion, cynicism, and inadequacy) relate to boys' and girls' aspirations. Performance in both domains was related to girls' educational aspirations, but only mathematics was linked to boys' aspirations. Positive within-domain relations from girls' motivational beliefs were also found, but their reading self-concept was negatively linked to their math-related occupational aspirations. For boys, only math-related motivational beliefs were associated with their aspirations. Lastly, school burnout was both directly and indirectly linked to students' aspirations. Overall, the study demonstrated the importance of including several factors when investigating students’ aspired educational degrees and occupational plans and, also, the added value of examining educational and occupational aspirations across academic domains.